Do fetiche à relíquia: paixão, luto e melancolia (?) a partir de um estudo de caso - Taveira Junior, Manoel Paulo (2014)
This work aims to investigate the origins and effects of passion through a case study. It is a study of the psychoanalytic clinic that aims to articulate metapsychological concepts of S. Freud's work taking as spine the history of the subject in question. The first chapter is dedicated to discuss the concepts of object-choice and fetishism. The second chapter is devoted to investigate and discuss the concept of the Oedipus complex, ideal Self, and the experience of illusion inherent passions. The third chapter discusses the concepts of mourning and melancholia. Clinical material are presented in each chapter to illustrate the chosen metapsychological concepts and indicate vividly the suffering experienced by the subject of the case, as well as his ability to "cure"